Constraints on Oil Palm Plantation in Kanagarian Rabi Jonggor, Gunung Tuleh District, West Pasaman Regency (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
Palm oil is one of the mainstay commodities for the national economy and is the country's largest foreign exchange earner in the non-oil and gas sector. Oil palm plantations in West Pasaman were originally developed by companies that established their companies in West Pasaman, this oil palm planting was due to the climatic conditions of West Pasaman which were very suitable for various plantation commodities. Nagari Rabi Jonggor is one of the nagari located in Gunung Tuleh District, West Pasaman Regency which has a large oil palm plantation. There are several obstacles in oil palm plantations in Kanagarian Rabi Jonggor namely; suitability of land for oil palm, seeds or superior varieties, access to fertilizers, labor, plant cultivation technology, marketing of products, and capital. By conducting an analysis using the Interpretative Structural Modeling (ISM) model, there are four sub-elements that have high driver power and low dependency, namely: E1 (Land suitability for oil palm), E7 (capital), E2 ( Superior seeds or varieties), and E3 (Access to fertilizers). Obstacles in oil palm plantations in Nagari Rabi Jonggor, Gunung Tuleh District, West Pasaman Regency, there are five levels, and the priority directions in overcoming obstacles in oil palm plantations are land suitability for oil palm and capital.